Correlation Between CHA2DS2-VASc Score and Left Atrial Size in Patients With Atrial Fibrillation: A More Than 15-Year Prospective Follow-Up Study - Tsai, Chin-Feng; Huang, Pang-Shuo; Chen, Jien-Jiun; Chang, Sheng-Nan; Chiu, Fu-Chun; Lin, Ting-Tse; Lai, Ling-Ping; Hwang, Juey-Jen; Tsai, Chia-Ti (Frontiers in Cardiovascular Medicine, 2021)
Background: Left atrial (LA) size represents atrial fibrillation (AF) burden and has been shown to be a predictor for AF stroke. The CHA2DS2-VASc score is also a well-established predictor of AF stroke. It is unknown to cardiologists whether these two risk scores are correlated, whether both are independent prognostic predictors and complimentary to each other, or whether one of them is a major determinant of stroke risk for AF patients. Method: A total of 708 patients from the National Taiwan University Atrial Fibrillation Registry were longitudinally followed up for more than 15 years. Left atrial size was measured by M mode of echocardiography. Adverse thromboembolic endpoints during follow-up were defined as ischemic stroke or transient ischemic attack. Results: The mean age was 72.1 ± 12.9 years, with 53% men. Both LA size and CHA2DS2-VASc score were associated with the risk of stroke in univariate analyses. There was a weak but significant positive correlation between LA size and CHA2DS2-VASc score (r = 0.17, P < 0.0001). Patients with higher CHA2DS2-VASc scores had a higher mean LA size (P < 0.01 for trend). When combining LA size and CHA2DS2-VASc score in the multivariable Cox model, only CHA2DS2-VASc score remained statistically significant [HR 1.39 (1.20–1.63); P < 0.001]. Conclusion: LA size is not an independent predictor of AF stroke, and calculation of CHA2DS2-VASc score may be an alternative to measurement of echocardiographic LA size when evaluating the risk of stroke for AF patients.